Comparison of Freeze Protection Methods for Strawberry Production in Florida. Issue 1 (2nd January 2016) - Hernandez, Ixchel M.; Santos, Bielinski M.; Stanley, Craig D.; Zhao, Xin
Abstract: During strawberry (Fragaria × ananassa) freeze protection, the standard practice is applying sprinkler irrigation on plant canopies to prevent and reduce freezing damage. This method is highly inefficient because it uses large volumes of water. The overall goal of this study was to compare the effects of freeze protection methods on water savings, and growth and fruit weight of strawberry. Treatments consisted of the following: sprinkler heads delivering 17 L∙min –1, sprinkler heads delivering 13 L∙min –1, light-weight row covers (21 g∙m –2 ) on the crop canopy, light-weight row covers on 60-cm-high mini-tunnel hoops, heavy-weight row covers (31 g∙m –2 ) on the crop canopy, heavy-weight row covers on 60-cm-high mini-tunnel hoops, and foliar application of a polymer (Desikote). There were eight freezing and near freezing nights (≤1.1 °C) at the experimental site during both seasons with a minimum air temperature of –2.8 °C. Minimum temperature inside the row covers ranged between 0.6 to 4.4 °C at the canopy level. There were significant treatment effects on early and total marketable fruit weights. The highest early marketable fruit weight was found in plots protected with light-weight row covers with hoops, heavy-weight row covers on canopy, and foliar polymer, ranging between 5.0 to 5.5 t∙ha –1 . For total marketable fruit weight, using non-irrigation methods resulted in the highest fruit weight with 23.0 t∙ha –1 . In conclusion, data showed that using non-irrigation techniques provided satisfactory freeze protection under the evaluated conditions and increased total marketable fruit weight, possibly due to reduced injury of fruits and flowers when using alternative techniques.